2016
DOI: 10.3171/2016.8.focus16266
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus associated with childhood nonaccidental head trauma

Abstract: OBJECTIVE The incidence of posttraumatic ventriculomegaly (PTV) and shunt-dependent hydrocephalus after nonaccidental head trauma (NAHT) is unknown. In the present study, the authors assessed the timing of PTV development, the relationship between PTV and decompressive craniectomy (DC), and whether PTV necessitated placement of a permanent shunt. Also, NAHT/PTV cases were categorized into a temporal profile of delay in admission and evaluated for association with out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Hydrocephalus is a disease in which excessive secretion, circulation and absorption of cerebrospinal fluid (CSF) are impaired by craniocerebral diseases, resulting in increased intracranial CSF levels, expansion of the ventricular system and progressive expansion of the subarachnoid space 1 . Hydrocephalus can be primary or secondary to trauma, spontaneous bleeding, infection and tumours and can also be comorbid with neurological diseases such as dementia, Alzheimer's disease and Parkinson's disease 2‐4 . Hydrocephalus is a great challenge in neurosurgery because of its complicated aetiology, unclear mechanism, difficult treatment and many complications.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocephalus is a disease in which excessive secretion, circulation and absorption of cerebrospinal fluid (CSF) are impaired by craniocerebral diseases, resulting in increased intracranial CSF levels, expansion of the ventricular system and progressive expansion of the subarachnoid space 1 . Hydrocephalus can be primary or secondary to trauma, spontaneous bleeding, infection and tumours and can also be comorbid with neurological diseases such as dementia, Alzheimer's disease and Parkinson's disease 2‐4 . Hydrocephalus is a great challenge in neurosurgery because of its complicated aetiology, unclear mechanism, difficult treatment and many complications.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological and neurodegenerative conditions in the brain can result in an increase in the release of inflammatory mediators into the injured areas. These conditions can include head trauma, intracranial hemorrhage, infection, brain tumor, genetic defect, or neurodegenerative disease (11,13,16,18,20,21,27,29,45,46). In many of these cases, the development of transient or chronic enlargement of the brain ventricles and an increase in pressure due to the accumulation of cerebrospinal fluid (CSF) occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Microglia, the macrophage-like cells of the central nervous system (CNS), can be triggered to release proinflammatory cytokines in response to abnormal protein accumulation or neuronal injury from chemical or physical means (7,50). It is possible that such inflammation is associated with increases in CSF production associated with neurological disease (4,17,18,35,46). Summarized in Table 1, proinflammatory cytokines found upregulated in neurodegenerative states include interleukin (IL)-1␤ and tumor necrosis factor-␣ (TNF-␣).…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, acquired hydrocephalus can develop at any age secondary to trauma, tumors, and meningoencephalitis leading to obstructions in the ventricular system [21]. In humans, the incidence rate of ventricular dilation occurring after a severe traumatic head injury is known to be about 39–44%, and increased ventricular size was found to be evident 4 weeks after sustaining an injury [23]. One report showed that the prevalence of hydrocephalus among dogs with head trauma was 26% (7/27), which was concluded to be an incidental finding [24].…”
Section: Discussionmentioning
confidence: 99%